2018
DOI: 10.3390/nu10101549
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin Prevents Nitric Oxide Deficiency-Induced Cardiovascular Remodeling in Rats via Suppressing TGF-β1 and MMPs Protein Expression

Abstract: Hesperidin is a major flavonoid isolated from citrus fruits that exhibits several biological activities. This study aims to evaluate the effect of hesperidin on cardiovascular remodeling induced by n-nitro l-arginine methyl ester (l-NAME) in rats. Male Sprague-Dawley rats were treated with l-NAME (40 mg/kg), l-NAME plus hesperidin (15 mg/kg), hesperidin (30 mg/kg), or captopril (2.5 mg/kg) for five weeks (n = 8/group). Hesperidin or captopril significantly prevented the development of hypertension in l-NAME ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 57 publications
3
26
0
1
Order By: Relevance
“…uPA is a plasmin activating pro‐matrix metalloproteinases in the cardiovascular system 26 . uPA binding to its receptor (uPAR) plays a pivotal role in signalling functions which influence cell behaviours including cell adhesion, surface proteolysis, migration, proliferation, chemotaxis and cell extravasation 27 .…”
Section: Discussionmentioning
confidence: 99%
“…uPA is a plasmin activating pro‐matrix metalloproteinases in the cardiovascular system 26 . uPA binding to its receptor (uPAR) plays a pivotal role in signalling functions which influence cell behaviours including cell adhesion, surface proteolysis, migration, proliferation, chemotaxis and cell extravasation 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the impairment of LV function has been demonstrated in rats that have received L-NAME, supported by a reduced maximum +LVdP/dt and minimum −LVdP/dt, ejection fraction (EF), stroke volume (SV), and fraction shortening (FS) [8,9]. There is substantial evidence to support the pathological process of cardiac remodeling associated with the renin-angiotensin system (RAS), oxidative stress, and inflammation [10][11][12][13]. Angiotensin II (Ang II) induces cardiomyocyte hypertrophy via binding to angiotensin II receptor type I (AT 1 R) and activating various intracellular signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Hesperidin has been assessed in studies on rats and humans and shown to have beneficial effects on several parameters related to the cardiovascular system and the improvement of CVRFs, such as decreasing blood pressure, [ 8–11 ] improving endothelium‐dependent vasodilation during hypertension, [ 12 ] decreasing total cholesterol and triglyceride levels, [ 13 ] improving glucose and insulin levels and the homeostasis model assessment index, [ 14 ] decreasing inflammatory markers, [ 9 ] decreasing kidney damage markers, [ 15 ] and decreasing oxidative stress. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%